Police officer discipline and appeal system in South Korea: focusing on police officer discipline under the Myung-bak Lee (MB) administration from 2008 to 2012. (18th May 2016) - Kim, Sangwoon; Doh, Soogwan
Abstract : This study seeks to explore the role of the appeal system in the police officer discipline process and to analyse the impact of the appeal on disciplinary decision or corrective action at the individual level. We conducted this investigation by using empirical models with approximately 5500 samples collected in South Korea. Before exploring the role of the appeal system and empirically analysing its impact on disciplinary decisions, this study reviews the literature on public official discipline and appeal procedures, provides an overview of the recent police officer discipline and appeal process and describes the distribution of the number of discipline and appeals, by breach type and year, in South Korea. To analyse the impact of appeal on disciplinary decisions, this study accounts for various characteristics which are believed to affect disciplinary decisions. Results from the logistic regression and ordinary least squares regression model indicate that a higher level of disciplinary action is related to the likelihood of an individual taking an appeal which is subsequently attenuated. The results also show that suspension and dismissal for the misconduct of police officers are more attenuated than other disciplinary decisions. Findings reveal strong support for the hypothesised impact of the appeal system on the disciplinary decision at the individual level. These findings have important implications for the direction of reform for the current appeal system and police officer disciplinary system in South Korea as well as for future research.